2013
DOI: 10.1523/jneurosci.2093-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Receptor Activation Decreases Excitability of Cortical Interneurons by Inhibiting α7 Nicotinic Receptors

Abstract: Many proteins in the immune system are also expressed in the brain. One such class of immune proteins are T-cell receptors (TCRs), whose functions in T lymphocytes in adaptive immunity are well characterized. In the brain, TCRs are confined to neocortical neurons, but their functional role has not been determined. In mouse layer 1 neocortical neurons, TCR activation inhibited ␣7 nicotinic currents. TCRs modulated ␣7 currents via tyrosine phosphorylation of ␣7 nicotinic receptors (nAChRs) through src tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 53 publications
3
42
1
Order By: Relevance
“…Effects of genistein or specific Src-family kinase inhibitors were observed both on reconstituted a7 nAChRs expressed in Xenopus oocytes or cell lines as well as on native receptors and confirmed that activity of a7 nAChRs can be modulated by phosphorylation (Charpantier et al, 2005). More recent experiments confirmed the relevance of T cell receptors in the phosphorylation and modulation of a7 nAChRs in the brain (Komal et al, 2014). Activation of T cell receptors, expressed in neocortical neurons, Fig.…”
Section: B Functional Properties Of A7 Nicotinic Acetylcholine Recepsupporting
confidence: 62%
“…Effects of genistein or specific Src-family kinase inhibitors were observed both on reconstituted a7 nAChRs expressed in Xenopus oocytes or cell lines as well as on native receptors and confirmed that activity of a7 nAChRs can be modulated by phosphorylation (Charpantier et al, 2005). More recent experiments confirmed the relevance of T cell receptors in the phosphorylation and modulation of a7 nAChRs in the brain (Komal et al, 2014). Activation of T cell receptors, expressed in neocortical neurons, Fig.…”
Section: B Functional Properties Of A7 Nicotinic Acetylcholine Recepsupporting
confidence: 62%
“…Our lab has shown that activation of TCRs decreases neuronal excitability of layer 1 interneurons of the prefrontal cortex through attenuation of a7 nAChR activity [9]. This TCR mediated partial brake on a7 nAChR activity is conveyed by endogenous basal activation of TCRs in the CNS as neurons recorded from TCRb knockout mice had significantly larger a7 nicotinic currents than neurons recorded from wildtype mice.…”
Section: Tcr Expression and Physiological Role In The Nervous Systemmentioning
confidence: 94%
“…Furthermore, intercellular signaling mediated via receptor tyrosine kinases such as insulin receptors [31,32], which bind to released insulin, and TrkB receptors [33,34], which bind to released brain-derived neurotrophic factor, negatively modulates a7 nAChR currents similar to the actions of TCRs [9]. This begs the question why would neurons need this extra redundancy of another membrane receptor, namely the TCR, that ultimately signals through tyrosine kinases?…”
Section: Potential Physiological Roles Of the Mhc-tcr Receptor Complementioning
confidence: 99%
See 2 more Smart Citations